2010
DOI: 10.4149/gpb_2010_01_59
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiofrequency radiation on DNA and lipid damage in non-pregnant and pregnant rabbits and their newborns

Abstract: The concerns of people on possible adverse health effects of radiofrequency radiation (RFR) generated from mobile phones as well as their supporting transmitters (base stations) have increased markedly. RFR effect on oversensitive people, such as pregnant women and their developing fetuses, and older people is another source of concern that should be considered. In this study, oxidative DNA damage and lipid peroxidation levels in the brain tissue of pregnant and non-pregnant New Zealand White rabbits and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 30 publications
(34 reference statements)
0
13
0
1
Order By: Relevance
“…We also identified parallel morphological and functional changes in hippocampal and mPFC neurons, though the molecular mechanisms responsible for the effects remain unclear. Lower RF-EMR density and long-term (chronic) exposure-induced cellular/organismal responses have previously been suggested to involve activation of signal transduction pathways, disruption of ion channels, DNA damage, and changes to cellular apoptosis and gene expression163334. We used acute, single, high-density RF-EMR exposure, and showed a fast and long-term positive effect on recognition memory.…”
Section: Discussionmentioning
confidence: 98%
“…We also identified parallel morphological and functional changes in hippocampal and mPFC neurons, though the molecular mechanisms responsible for the effects remain unclear. Lower RF-EMR density and long-term (chronic) exposure-induced cellular/organismal responses have previously been suggested to involve activation of signal transduction pathways, disruption of ion channels, DNA damage, and changes to cellular apoptosis and gene expression163334. We used acute, single, high-density RF-EMR exposure, and showed a fast and long-term positive effect on recognition memory.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, human lymphocytes were exposed to 2459 MHz pulsed MW for 2 h, at a power density of 5 mW/cm 2 and SAR of 2.135 W/kg, and there was no evidence of induction of DNA single-strand breaks and alkali labile lesions either immediately or 4 h after exposure (Vijayalaxmi et al 2000(Vijayalaxmi et al , 2001a(Vijayalaxmi et al , 2001b. However, a few groups (Campisi et al 2010, Guler et al 2010, Franzellitti et al 2010) have reported positive effects on DNA damage after intermittent exposure but showed no effects on the same end point with CW 900/1800 MHz exposure. On the other hand, previous work from our research group has reported no effects on human leukaemic Tcells (Jurkat cells) after CW and Pulse-modulated (PM) 915 MHz exposure (Cranfield et al 2001).…”
Section: Discussionmentioning
confidence: 91%
“…They concluded that increased oxidative stress due to the EMF exposure may contribute to cognitive impairment and inflammation in the brain. The lipid peroxidation in the brain tissue of pregnant and non-pregnant New Zealand White rabbits exposed to 1800 MHz RF-EMF, resulting in oxidative DNA damage, was investigated by Guler et al [25]. Rabbits were exposed to RF-EMF (1800 MHz GSM; 14 V/m) for 15 min/ day during 7 days.…”
Section: Discussionmentioning
confidence: 99%